Implementasi Kebijakan Perubahan Nomenklatur Jabatan Pelaksana Aparatur Sipil Negara di Badan Penanggulangan Bencana Daerah Kota Surabaya - Ramadhan, Roif Rizaly; Hertati, Diana (IAI Nasional Laa Roiba Bogor, 2024)
This article aims to gain a deeper understanding of how the implementation of the Minister of Administrative Reform and Bureaucratic Reform Regulation Number 11 of 2024 concerning changes in the nomenclature of executive positions of the State Civil Apparatus in BPBD Surabaya City is proceeding. This research employs a descriptive qualitative approach, which will provide valuable insights into the implementation of policies on changes in the nomenclature of executive positions in BPBD Surabaya City, as well as the factors that influence it. BPBD has identified four variables as factors for successful policy implementation, namely communication, resources, disposition, and bureaucratic structure. The results of this study indicate that the implementation of the policy implementation of the Minister of Administrative Reform and Bureaucratic Reform Regulation Number 11 of 2024 is well underway. This is indicated by the variables that have been realised to a certain extent, but it is a gradual process that will take time. It would be beneficial for other agencies to consider the importance of maintaining the synergy of leaders and staff to carry out all bureaucratic reform activities, as emphasised in this study. The insights gained from this research could prove valuable for improving the effectiveness of policy implementation related to changes in the nomenclature of executive positions within the Surabaya City government.